Potassium tert-Butoxide Promoted α-Keto Ester Synthesis through C(O)–N Bond Cleavage of Isatins - Ghosh, Tridev; Basak, Soumya Jyoti; Dash, Jyotirmayee (Synlett, 2024)
We present a novel and cost-effective method for synthesizing biologically important α-keto esters in a single-step reaction. This approach involves a sequential cascade process within a single reaction vessel facilitated by t-BuOK, which promoted the cleavage of the sp2 C(O)–N bond of an isatin and the formation of a new N–C(sp2)(O) bond with benzoyl chloride. To the best of our knowledge, this is the first instance of the construction of an α-keto ester scaffold adjacent to an amide group through a one-pot process. In comparison to existing methods, our protocol offers several advantages: readily available starting materials, mild reaction conditions, a concise synthetic pathway, high sustainability, and excellent tolerance towards various functional groups. Given these strengths, we anticipate widespread use of this method in the synthesis of related α-keto ester scaffolds.
Keywords: keto esters; isatins; benzoyl chloride; C–N bond cleavage; transition-metal-free reaction